Influence of perinatal and childhood exposure to tobacco and mercury in children’s gut microbiota - Pérez-Castro, Sonia; D’Auria, Giuseppe; Llambrich, Maria; Fernández-Barrés, Sílvia; Lopez-Espinosa, Maria-Jose; Llop, Sabrina; Regueiro, Benito; Bustamante, Mariona; Francino, M. Pilar; Vrijheid, Martine; Maitre, Léa (Frontiers in Microbiology, 2024)
Background: Early life determinants of the development of gut microbiome composition in infancy have been widely investigated, however if early life pollutant exposures, such as tobacco or mercury, have a persistent influence on the gut microbial community after its stabilization at later childhood remains largely unknown.In this exposome-wide study, we aimed at identifying the contribution of exposure to tobacco and mercury from the prenatal period to childhood, to individual differences in the fecal microbiome composition of 7-year-old children, considering co-exposure to a width of established lifestyle and clinical determinants.Methods: Gut microbiome was studied by 16S rRNA amplicon sequencing in 151 children at genus level. Exposure to tobacco was quantified during pregnancy through questionnaire (active tobacco consumption, 1 secondhand smoking -SHS)-and biomonitoring (urinary cotinine), at 4 years (urinary cotinine, SHS) and at 7 years (SHS). Exposure to mercury was quantified during pregnancy (cord blood) and at 4y (hair). Forty nine other potential environmental determinants (12 at pregnancy/birth/infancy, 15 at 4y and 22 at 7y, such as diet, demographics, quality of living/social environment and clinical records) were registered. We used multiple models to determine microbiome associations with pollutants including multi-determinants multivariate analysis of variance and linear correlations (wUnifrac, Bray-Curtis, Aitchison, ß-diversity distances), singlepollutant permutational multivariate analysis of variance adjusting for co-variates (Aitchison), and multivariable association model with single taxa (MaAsLin2; genus). Sensitivity analysis was performed including genetic data in a subset of 107 children.Results: Active smoking in pregnancy was systematically associated with microbiome composition, ßdiversity (R 2 2-4%, p < 0.05, Aitchison), independently of other co-determinants. However, in the adjusted single pollutant models (PERMANOVA), we did not find any significant association. An increased relative abundance of Dorea and decreased of Akkermansia was associated with smoking during pregnancy (q < 0.05).Discussion: Our findings suggest a long-term sustainable effect of prenatal tobacco exposure on the children's gut microbiota. This effect was not found for mercury exposure or tobacco exposure during childhood. Assessing the role of these exposures on the children's microbiota considering multiple environmental factors should be further investigated.